2022
DOI: 10.3389/fneur.2021.698206
|View full text |Cite
|
Sign up to set email alerts
|

Developing Biomarkers of Mild Traumatic Brain Injury: Promise and Progress of CNS-Derived Exosomes

Abstract: Mild traumatic brain injuries (mTBI) are common injuries across civilian and military populations. Although most individuals recover after mTBI, some individuals continue to show long-term symptoms as well as increased risk for neurodegenerative and neuropsychiatric disorders. Currently, diagnosing TBI severity relies primarily on self-report and subjective symptoms, with limited tools for diagnosis or prognosis. Brain-derived exosomes, a form of extracellular vesicle, may offer a solution for interpreting inj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 111 publications
(193 reference statements)
0
14
0
Order By: Relevance
“…Among EVs, exosomes are of particular interest due to the ability of their miRNA cargo to modulate the gene expression pattern in recipient cells and induce systemic inflammation [ 21 , 22 , 23 ]. Such a role is highlighted in the work of Long et al [ 24 ], who carried out an experimental study in which TBI brain extracts were used to stimulate the production of exosomes in primary cultured astrocytes; once detected by immunofluorescence, exosomes were separated from astrocytes and added to primary cultured microglia.…”
Section: Traumatic Brain Injury and Exosome-derived Mirnasmentioning
confidence: 99%
“…Among EVs, exosomes are of particular interest due to the ability of their miRNA cargo to modulate the gene expression pattern in recipient cells and induce systemic inflammation [ 21 , 22 , 23 ]. Such a role is highlighted in the work of Long et al [ 24 ], who carried out an experimental study in which TBI brain extracts were used to stimulate the production of exosomes in primary cultured astrocytes; once detected by immunofluorescence, exosomes were separated from astrocytes and added to primary cultured microglia.…”
Section: Traumatic Brain Injury and Exosome-derived Mirnasmentioning
confidence: 99%
“…The quantification of EVs as a biomarker has been investigated in studies using serum and plasma-derived EVs without sample enrichment for specific EV subtypes (Younas et al, 2022 ). The majority of attempts to establish EV-derived biomarkers of TBI have centered on leveraging the presence of traditionally investigated blood-derived proteins inside EVs for diagnosis and evaluating neurological impairments predicting the outcome (Winston et al, 2019 ; Vaughn et al, 2021 ).…”
Section: Evs As Diagnostic and Therapeutic Conduits In Tbi: Examining...mentioning
confidence: 99%
“…As a result, there is an unmet clinical need for accurate biomarkers that can identify all TBIs, including mTBI, and predict the likelihood of developing long-term sequelae, including post-concussive syndrome chronic traumatic encephalopathy (Ghaith et al, 2022 ; Mavroudis et al, 2022 ). Recent research has revealed that circulating exosomes enriched for CNS-specific tissue sources may be a method to develop practical biomarkers for TBI, particularly mild TBI, to circumvent these difficulties (Goetzl et al, 2019 , 2020 ; Winston et al, 2019 ; Vaughn et al, 2021 ).…”
Section: Evs As Diagnostic and Therapeutic Conduits In Tbi: Examining...mentioning
confidence: 99%
See 1 more Smart Citation
“…A traumatic cerebral concussion can induce mild traumatic brain injury (mTBI), accounting for 75% of all reported cases of head injury, and mTBI can cause various debilitating symptoms, including headaches, irritability, fatigue, attention deficits, sleep disturbances, depression, and anxiety [ 1 , 2 ]. However, the incidence of mTBI is grossly underestimated since most individuals completely recover within the first days to weeks after injury, preventing them from seeking medical treatment [ 3 ]. People with sustained single mTBI have an increased risk of developing repetitive mTBI (rmTBI) [ 4 ].…”
Section: Introductionmentioning
confidence: 99%